Kristen Koptik Mesir - Masyhur, Ahmad (Jurnal ICMES, 2020)
The number of Coptic Christians in Egypt continues to decline. This article aims to analyze the main factors causing discrimination faced by Coptic Christians in their homeland and analyze the impact of this discrimination on Coptic Christians. In this study, researchers used Lewis A. Coser's conflict theory to analyze the main problems that exist. This research resulted in the finding that there were factors that triggered discrimination against Coptic Christians. These factors come from two sides, namely from government and non-government. Besides, this study finds, discrimination also had a positive impact, such as the strengthening of their group solidarity, the stronger their identity as natives of the Pyramid country, and the more proud they were to maintain their identity as Coptic Christians.